Photovoltaic cells with transparency for glass coverage: case study in party space - Dos Santos, Christian Antonio; Vendruscolo, Ágata; Rogovski, Bruna; REIS, Mari Aurora Favero (Latin American Journal of Energy Research, 2024)
Sustainable energy and technological development in electricity generation processes offer opportunities for the development and utilization of new photovoltaic technologies in construction. Photovoltaic cells for glazed surfaces, known as double glass or double-skin, have been applied in modern buildings due to their attributed characteristics that can enhance thermal comfort, provide natural lighting for internal areas, ensure privacy in external environments, and reduce energy consumption. The objective of this study is to investigate the viability of using double glass in the glazed roof of a family party venue. The qualitative method, a case study, was employed to assess the demand for electrical energy in the building and the potential use of double glass photovoltaic technologies. Market research was initially conducted with technology suppliers, enabling the evaluation of characteristics for the technological and economic feasibility of the project. The results show that the installation of double glass photovoltaic technology offers 40% transparency to solar radiation through the roof, resulting in thermal and luminous comfort. In terms of economic viability, the study demonstrates the possibility of return on investment in 4.6 years, considering energy generation, reduced building energy costs, and installation expenses. The installation of double glass technology, according to market research, is economically viable and generates local electrical energy for residents, providing comfort in the environment and enhancing the quality of life for occupants.